Analisa faktor-faktor yang berhubungan dengan pemberian ASI eksklusif Di wilayah kerja Puskesmas Prabumulih Timur Kota Prabumulih Tahun 2021 - Desi Ratnasari; Sendy Pratiwi Rahmadhani; Tuti Farida; Siti Aisyah (Universitas Batanghari Jambi, 2021)
Exclusive breastfeeding is given to infants aged 0-6 months, because the best nutrition for babies is only obtained through breast milk (WHO, 2020). According to data from the World Health Organization (WHO) worldwide exclusive breastfeeding coverage is only around 44 percent during the 2015-2020 period. Based on data from the 2019 Indonesian health profile, it is stated that the percentage of exclusive breastfeeding coverage in Indonesia for infants 0-6 months is 67.74 percent. Exclusive breastfeeding coverage in Prabumulih City in 2019 was 65.8 percent. The results of a preliminary study at the Prabumulih Timur Health Center covered only 43.1 percent of exclusive breastfeeding. The results showed that from 78 respondents. It was found that those who gave exclusive breastfeeding were 38 (48.7%) and those who did not gave exclusive breastfeeding were 40 (51.3%), low level of education 44 (56.4%) and higher education 34 (43.6%). working mothers 44 (56.4%) and mothers who did not work 34 (43.6%), low parity 30 (38.5%) and high parity 48 (61.5%), normal delivery 59 (75.6% ) and CS 19 delivery (24.4%). chi-square results 4 (four) significant variables with p-value <0.05, namely education level variable p-value = 0.013, OR = 0.280 (95% CI = 0.109-0.714), employment status p-value = 0.002 , OR = 0.193 (95% CI = 0.073-0.514), parity with p-value = 0.023, OR = 3.333 (95% CI = 1.279-8.688), delivery process with p-value = 0.012, OR = 5.100 (95% CI= 1,509-17,237). The conclusion in this study is that there is a relationship between parity and the process of giving birth simultaneously with exclusive breastfeeding in the working area of the Prabumulih Timur Health Center, Prabumulih City in 2021. It is recommended that the community give exclusive breastfeeding to their babies in order to prevent infant morbidity.